Penerapan Media Powerpoint Dalam Meningkatkan Hasil Belajar PAI Pada Siswa Kelas X Desain Komunikasi Visual Di SMK Teknologi Plus Padang - Harahap, Eva Delima (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to enhance student engagement and learning outcomes through the use of PowerPoint media in Islamic Religious Education (PAI) lessons on the topic of undesirable character traits. The classroom action research was conducted in two cycles, encompassing planning, implementation, observation, and reflection stages. The findings indicate a significant improvement in student engagement and learning outcomes from Cycle I to Cycle II. In Cycle II, the class-wide mastery level reached 90%, demonstrating the effectiveness of PowerPoint as a teaching aid. This media facilitated students' understanding of the material visually, motivated them, and encouraged more active interactions. Thus, the integration of multimedia-based technology is recommended in PAI lessons to improve student learning outcomes.